EFFECT OF ELECTRONIC PROCUREMENT TECHNICAL SUPPORT STAFF ON PROCUREMENT PERFORMANCE IN ENERGY SECTOR STATE CORPORATIONS IN KENYA - Muriuki, Jane Ireri; Guyo, Dr. Wario; Odhiambo, Prof. Romanus; Kinoti, Dr. Justus (International Journal of Supply Chain Management, 2019)
Purpose: The general objective of this study was to investigate the effect of electronic procurement technical support staff on procurement performance in the energy sector state corporations in Kenya. Methodology: The study adopted an exploratory approach using descriptive survey design and correlational design. The target population comprised 360 procurement staff and 25 electronic procurement technical support staff from 9 Energy Sector state corporations in Kenya. The sample size consisted of 211 respondents who included procurement and electronic procurement technical support staff. Simple random sampling and census techniques were used in the study. The key data collection instrument used in the study was the questionnaire. Qualitative data were analysed using content analysis while quantitative data was analysed with the help of SPSS widow. Multiple regression was used to test whether the independent variables have any effect on procurement performance. Results: The study findings indicated that electronic procurement technical support staff contributes positively to procurement performance. Based on the findings, it can be concluded that Electronic procurement technical support staff was found to have the strongest effect on procurement performance. The electronic procurement technical support staffs have the required technical knowledge to deliver products and services that support procurement processes. They were also able to quickly respond to ICT related technicalities. Unique Contribution to Theory, Practice and Policy: The study recommended that organizations that require to improve their procurement performance through use of ICT must invest heavily in their technical support staff.